Interações entre visitantes e o Museu Game Ciência e suas contribuições enquanto espaço de Divulgação Científica - RIBEIRO, Jordânia Araújo de Meneses (2024)
Science museums are considered an important source of knowledge, since they contribute significantly to scientific culture, formal and non-formal education in science, and through their exhibitions they provide visitors with experiences that arouse curiosity and interest about the themes developed there. The objective of this research focused on investigating the effects of scientific dissemination based on the interaction of visitors with the museum activities of the Game Science Museum. This is a study with a qualitative approach of a case study typology, in which data collection continued supported by steps that involved recording the views, categorization and analysis. To support the analysis, categories were developed based on a protocol for studying audiences in science museums and the sociocultural aspect with James Wertsch's Theory of Mediated Action. The categories were: types of interaction and conversations. In view of this organization, the research results were discussed according to the types of interaction observed and the content of the conversations based on James Wertsch's Theory of Mediated Action, allowing us to analyze the interactions of visitors from a sociocultural approach to learning. In our results, we observed that visitors' experiences highlight the contributions of these spaces to science education and highlight how learning can occur through interaction and collaboration during the visit. Visitors' opinions about the museum experience instigate reflection on the relevance of these environments for non-formal science education, as well as for the integration of games in the science teaching and learning process. The interactions show that museum activity fulfills the objective of fostering discussions, demonstrating that the learning process in non-formal teaching environments is in constant construction. We also emphasize the importance of internalizing the content covered in the school context and how they can be given new meanings in another context. Our research reiterates that science museums play a significant role in science education by promoting educational experiences, stimulating varied discussions on scientific and technological topics, and cultivating teenagers' enthusiasm, interest and motivation towards science.